Apilimod, a candidate anticancer therapeutic, arrests not only PtdIns(3,5)P2 but also PtdIns5P synthesis by PIKfyve and induces bafilomycin A1-reversible aberrant endomembrane dilation - Sbrissa, Diego; Naisan, Ghassan; Ikonomov, Ognian C.; Shisheva, Assia (PloS one, 2018)
PIKfyve, an evolutionarily conserved kinase synthesizing PtdIns5P and PtdIns(3,5)P2, is crucial for mammalian cell proliferation and viability. Accordingly, PIKfyve inhibitors are now in clinical trials as anti-cancer drugs. Among those, apilimod is the most promising, yet its potency to inhibit PIKfyve and affect endomembrane homeostasis is only partially characterized. We demonstrate here for the first time that apilimod powerfully inhibited in vitro synthesis of PtdIns5P along with that of PtdIns(3,5)P2. HPLC-based resolution of intracellular phosphoinositides (PIs) revealed that apilimod triggered a marked reduction of both lipids in the context of intact cells. Notably, there was also a profound rise in PtdIns3P resulting from arrested PtdIns3P consumption for PtdIns(3,5)P2 synthesis. As typical for PIKfyve inhibition and the concomitant PtdIns(3,5)P2 reduction, apilimod induced the appearance of dilated endomembrane structures in the form of large translucent cytoplasmic vacuoles. Remarkably, bafilomycin A1 (BafA1) fully reversed the aberrant cell phenotype back to normal and completely precluded the appearance of cytoplasmic vacuoles when added prior to apilimod. Inspection of the PI profiles ruled out restoration of the reduced PtdIns(3,5)P2 pool as a molecular mechanism underlying BafA1 rescue. Rather, we found that BafA1 markedly attenuated the PtdIns3P elevation under PIKfyve inhibition. This was accompanied by profoundly decreased endosomal recruitment of fusogenic EEA1. Together, our data demonstrate that apilimod inhibits not only PtdIns(3,5)P2 but also PtdIns5P synthesis and that the cytoplasmic vacuolization triggered by the inhibitor is precluded or reversed by BafA1 through a mechanism associated, in part, with reduction in both PtdIns3P levels and EEA1 membrane recruitment.